Commercialization of the gene-edited crop and morality: challenges from the liberal patent law and the strict GMO law in the EU - Li Jiang (New Genetics and Society, 2020)
The EU aspires to utilize the economic advantages of gene-editing technology on one hand and ensure human health and environmental safety on the other. Surrounding the fierce debates over emerging gene-edited plant, the current debate focused on the issue of whether the gene-edited crop should be within or outside the GMO law and its implication for innovation. It should not be forgotten that it is also involved in the complex patentability issues pertaining to the legal interpretation of the patent law. The gene-edited crop is governed by GMO regulations due to its potential risk to human health and environmental safety. But it is heavily patented, as patent regulations ignore its potential risk. This article examines the discrepancy of the gene-edited crop between the existing GMO law and the patent law and reveals the challenges to current EU jurisdiction, including the international trade impediment challenge, the patent monopoly challenge, the market confusion challenge, and the agricultural economy suspension challenge. In the end, this article argues that EU GMO regulations should be bridged with a patent system in facing the regulatory challenges from the gene-edited crop.